Analisis Perbandingan Kinerja Keuangan Shariah Antara Sharia Conformity And Profitability (SCNP) Dan Shariah Maqashid Index Pada Bank Umum Syariah Diindonesia - Dandi Gunawan; Nurlaila Nurlaila; Laylan Syafina (Jurnal Mutiara Ilmu Akuntansi, 2023)
In this study the measurement of financial performance at Islamic Commercial Banks in Indonesia is carried out based on sharia aspects which consist of Islamic financial performance and Islamic maqashid performance. This study aims to analyze the performance of Islamic banking, especially Islamic Commercial Banks in Indonesia during the five year period from 2018-2022. Which is measured using the Sharia Conformity and Profitability (SCnP) and the Sharia Maqashid Index (SMI). The data used are 5 Islamic Commercial Banks consisting of: Bank Muamalat Indonesia (BMI), Bank Mega Syariah (BMS), Bank BCA Syariah (BCAS), Bank Bukopin Syariah (BBS), Bank Aceh Syariah (BAS). The data source used in this research is secondary data. Data is obtained from the annual reports of BUS in Indonesia for 2018-2022 via the website of each Islamic Commercial Bank. The results of this study show that based on the graphs and rankings, the results of the comparison of SCnP and SMI during the 2018-2022 period show that Islamic Commercial Banks in Indonesia are in one quadrant, namely URQ (Upper Right Quadran), Bank Aceh Syariah (BAS) is ranked first, Banks Muamalat Indonesia (BMI) is ranked second, Bank BCA Syariah (BCAS) is ranked third, Bank Bukopin Syariah is ranked 4th, and Bank Mega Syariah is ranked fifth.